Socialist reconstruction of agriculture in the adyghe village (1928–1932) - Yuri A., Yakhutl (Kavkazologiya, 2025)
The article is devoted to the socialist modernization of the agricultural sector of the economy of Adygea (1928-1932). The relevance of the research is caused by the growing interest in the Stalin-ist period in Soviet history, which is linked by two historical facts: the history of the USSR as a world power, which was formed during the reign of I. Stalin and socialist modernization. It was during the first five-year plan that the model of the socialist economy and industrial personnel was defined, including in the national formations of the USSR. National republics and autono-mous regions have gone through a period of socialist modernization, considering the peculiarities of their historical, economic, and cultural development. Such a national autonomy was Adygea. A weak level of agricultural development and a lack of industry characterized the region. These facts had a significant impact on the content of collectivization conducted in the late 1920s and early 1930s. During the period of mass collectivization, there is not only a transformation of the agri-cultural sector of the region's economy, but also the formation of national personnel in demand in regional industry, agriculture, cultural and educational spheres. The study makes it possible to identify regional features and patterns of formation of collective forms of management in Adygea as one factor of socialist modernization. In the process of reforming the agriculture of the region, training of national personnel was organized, who became active participants in the socialist transformations. Local authorities used violent, administrative methods against the rural popula-tion of Adygea, but the extent of their use was not critical. The author's conclusion is based on ar-chival documents used in the article. We emphasize that we ascribe this fact to a specific locality, but we do not believe it is representative of the entire Soviet peasantry during the collectivization period.